Frameworks of Movement Sciences - Miyashita, Mitsumasa (Applied sciences, 2023)
This article is composed of two parts. In the first part, a review is conducted on how research concerning human movement has been performed on Japanese subjects with newly developed methods in the last 60 years. In the second part, the frameworks of human movement sciences, such as exercise physiology, biomechanics, sports performance, and health, are proposed mainly based on the research results obtained by the author and his colleagues. It is expected that this article will be helpful to researchers in the fields of physical education, sports, and health.